Assessing Dipterocarp Diversity at Soraya Research Station, Leuser Ecosystem - Essy Harnelly; Irma Fitri; Iqbar; Yunita; Hendrix Indra Kusuma (Postgraduate, University of Mataram, 2025)
The Soraya research station is a lowland tropical forest and is included in the management area of the Leuser Ecosystem. This research station has a very high potential for biodiversity. This study aimed to determine the number and types of members of the Dipterocarpaceae tribe and to calculate the quantitative parameters of the plant community. Data collection in this study was carried out using the squared plot method placed randomly at the research location. The analysis used is the Shannon-Wiener diversity index, relative density, relative frequency, relative dominance, and Importance Value Index. The results show that ten species of Dipterocarpaceae belong to various levels of growth, namely seedlings, saplings, poles, and trees. Species of the Dipterocarpaceae spread over 40 plots. Shorea multiflora (Burck) Symington is a species that shows a widespread level and high degree of dominance at the study site. Analysis of plant species diversity using the Shannon-Wiener Index shows that both forest types, primary and secondary, are classified into the high species diversity index.